Recent Changes in Deep Ventilation of the Mediterranean Sea; Evidence From Long-Term Transient Tracer Observations - Li, Pingyang; Tanhua, Toste (Frontiers in Marine Science, 2020)
The Mediterranean Sea is a small region of the global ocean but with a very active overturning circulation that allows surface perturbations to be transported to the interior ocean. Understanding of ventilation is important for understanding and predicting climate change and its impact on ocean ecosystems. To quantify changes of deep ventilation, we investigated the spatiotemporal variability of transient tracers (i.e. CFC-12 and SF6) observations combined with temporal evolution of hydrographic and oxygen observations in the Mediterranean Sea from 13 cruises conducted during 1987-2018, with emphasize on the update from 2011 to 2018. Spatially, both the Eastern and Western Mediterranean Deep Water (EMDW and WMDW) show a general west-to-east gradient of increasing salinity and potential temperature but decreasing oxygen and transient tracer concentrations. Temporally, stagnant and weak ventilation is found in most areas of the EMDW during the last decade despite the prevailing ventilation in the Adriatic Deep Water between 2011 and 2016, which could be a result of the weakened Adriatic source intensity. The EMDW has been a mixture of the older Southern Aegean Sea dense waters formed during the Eastern Mediterranean Transient (EMT) event, and the more recent ventilated deep-water of the Adriatic origin. In the western Mediterranean basin, we found uplifting of old WMDW being replaced by the new deep-water from the Western Mediterranean Transition (WMT) event and uplifting of the new WMDW toward the Alboran Sea. The temporal variability revealed enhanced ventilation after the WMT event but slightly weakened ventilation after 2016, which could be a result of combined influences from the eastern (for the weakened Adriatic source intensity) and western (for the weakened influence from the WMT event) Mediterranean Sea. Additionally, the Mediterranean Sea is characterized by a Tracer Minimum Zone (TMZ) at mid-depth of the water column attributed to the rapid deep ventilation so that the TMZ is the slowest ventilated layer. This zone of weak ventilation stretches across the whole Mediterranean Sea from the Levantine basin into the western basin.